Pengaruh Persepsi Dukungan Organisasi dan Keterlibatan Kerja terhadap Kinerja Organisasi Pemeritahan Kenagarian dengan Organizational Citizenship Behaviour (OCB) sebagai Variabel Mediasi - Doni Nofriadi Doni Nofriadi; Dedet Deperiky Dedet Deperiky; Gus Andri Gus Andri (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This study aims to examine the effect of perceived organizational support and work engagement on organizational performance, with organizational citizenship behavior (OCB) as a mediating variable. The research employed a quantitative method using a survey design. The respondents consisted of all officials and institutional members of the Nagari Government in Kenagarian Lubuk Alung, Lubuk Alung District, Padang Pariaman Regency, in 2023, totaling 142 individuals selected through a total sampling technique. Data were collected using questionnaires with a 5-point Likert scale and analyzed using PLS-SEM with the assistance of SmartPLS 4.0.9.5 software. The findings reveal that perceived organizational support does not significantly affect organizational performance, while work engagement and OCB have a significant effect on organizational performance. In addition, perceived organizational support and work engagement significantly influence OCB, and OCB mediates the relationship between perceived organizational support and work engagement and organizational performance.